Mesoscale-driven dispersion of early life stages of European eel - Munk, P.; Buongiorno Nardelli, B.; Mariani, P.; Bendtsen, J. (Frontiers in Marine Science, 2023)
The larvae of the European eel travel an extensive distance of about 5000 km from the spawning area in the Sargasso Sea to the European coasts. We here study the larval drift with focus on the effects of mesoscale processes, analyzing data from a targeted survey and modelling possible drift trajectories. The survey covered the initial distribution of larvae in the Subtropical Convergence Zone (STCZ) which is characterized by complex patterns of oceanic fronts and mesoscale eddies. During March-April 2014 sampling was carried out along north-south transects. Hydrography was described using vertical CTD casts and UCTD-profiles, and larval distributions assessed from hauls of a large ring net. Patterns in water mass distribution and particle dispersion dynamics were analyzed by reconstruction and diagnosis of mesoscale dynamics, combining satellite observations and Argo profiles. Lagrangian drift trajectories of eel larvae were subsequently simulated starting from a data-driven high resolution 3D reconstruction of the modelled flow. We found the area of larval distribution delimited by frontal zones, defined by the combined effects of marked longitudinal salinity gradients and large scale zonal temperature variations. Modelled patterns of eel larvae dispersion were predominantly influenced by the current shear and eddy strain, and while the direction was mainly westward, a significant dispersal was also observed in northeastward directions. Such almost isotropic transport of European eels is supported by historical data on larval size distribution, and results challenge common interpretations of eel larval drift which propose an initial westward advection of the entire population to the Gulf Stream along the offshore edge of the Antilles current.